2-{1- 2-(Bis{2- 1-(5-chloro-2-hydroxyphenyl)ethylideneamino ethyl}amino) ethyliminio ethyl}-4-chlorophenolate toluene hemisolvate - Lee, S.M.; Ng, S.W.; Lo, K.M.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
In the toluene hemisolvated tripodal tris(2-aminoethyl) amine Schiff base, C(30)H(33)Cl(3)N(4)O(3 center dot)0.5C(7)H(8), one of the three imino N atoms is protonated, forming a hydrogen bond with the O atom at an adjacent benzene ring. The other two imino N atoms act as hydrogen-bond acceptors from phenolate OH groups. The toluene solvent molecule is disordered about a centre of inversion.